Manometric evaluation of the interdigestive antroduodenal motility in subjects with fasting bile reflux, with and without antral gastritis. Issue 4 (April 1989) - Testoni, P A; Fanti, L; Bagnolo, F; Passaretti, S; Guslandi, M; Masci, E; Tittobello, A
Abstract : The interdigestive antroduodenal motor activity was studied in 15 patients with bile reflux without gastritis (group A), 17 with bile reflux and chronic antral superficial gastritis (group B) and in nine healthy controls (group C), by manometric recording of phases of the interdigestive motility complex (IDMC) over 240 minutes, or until two consecutive migrating motor complexes (MMCs) had been recorded, whichever the shorter. In the patients with bile reflux the occurrence of MMCs was decreased and median duration of the IDMC was significantly prolonged (group A = 162.5 min; group B = 185.0 min), compared with controls (group C = 92.0 min; p less than 0.01 v groups A and B). There were no differences in motility pattern between patients with and without gastritis, suggesting that motor abnormalities are not caused by gastritis, but may precede its occurrence. Delayed occurrence of motor activity fronts increases duodenogastric reflux, but correlation with gastric mucosal lesions was not shown, suggesting that other mechanisms are involved.